Quantification of heat shock proteins in the posterior interosseous nerve among subjects with type 1 and type 2 diabetes compared to healthy controls - Ising, Erik; Åhrman, Emma; Thomsen, Niels O. B.; Åkesson, Anna; Malmström, Johan; Dahlin, Lars B. (Frontiers in Neuroscience, 2023)
Introduction: Diabetic peripheral neuropathy (DPN) is a common complication to both type 1 (T1D) and type 2 diabetes (T2D). No cure for DPN is available, but several potential targets have been proposed for treatment. Heat shock proteins (HSPs) are known to respond to both hyper-and hypoglycaemia. DPN can be diagnosed using electrophysiology and studied using peripheral nerve biopsies.To study presence and patterns of HSPs in peripheral nerve biopsies from subjects with T1D, T2D and healthy controls.Methods: Posterior interosseous nerves (PIN) from a total of 56 subjects with T1D (n = 9), T2D (n = 24) and without diabetes (i.e., healthy controls, n = 23) were harvested under local anaesthesia and prepared for quantitative mass spectrometry analysis. Protein intensities were associated to electrophysiology data of ulnar nerve and morphometry of the same PIN, and differences in protein intensities between groups were analysed.In total, 32 different HSPs were identified and quantified in the nerve specimens. No statistically significant differences were seen regarding protein intensities between groups. Furthermore, protein intensities did not correlate to amplitude or conduction velocity in ulnar nerve or with myelinated nerve fibre density of PIN.Quantitative proteomics can be used to study HSPs in nerve biopsies, but no clear differences in protein quantities were seen between groups in this cohort.